Earth chemistry - Cobb, Allan B. (New York : Chelsea House, 2009)
Explains chemical and physical changes on Earth, exploring how the atmosphere, hydrosphere, lithosphere, and biosphere relate and interact with one another.
Earth -- The atmosphere -- Chemical processes in the atmosphere -- The hydrosphere -- Chemical and physical processes in the hydrosphere -- The lithosphere -- Chemical processes in the lithosphere -- Biosphere.
Description based on print version record.
Includes bibliographical references (p. 120-121) and index.
Keywords: Environmental chemistry -- Juvenile literature; Environmental chemistry; Chemistry; Electronic books; Electronic books